2021
DOI: 10.1093/infdis/jiab537
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Clofazimine and Atovaquone as a Potent Therapeutic Regimen for the Radical Cure of Babesia microti Infection in Immunocompromised Hosts

Abstract: Human babesiosis caused by Babesia microti can be fatal in immunocompromised patients, and the currently used drugs are often ineffective. A recent study found that clofazimine clears B. microti Munich strain in immunocompromised mice. In the present study, we investigated the efficacies of clofazimine and 2-drug combinations involving clofazimine, atovaquone, and azithromycin against B. microti Peabody mjr strain in immunocompromised mice. Treatment with clofazimine alone, clofazimine plus azithromycin, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In this study, we used a combination of half the dose of CFZ with half the dose of NTZ. This was based on observations from previous studies of Tuvshintulga et al (2021) who reported excellent efficacy and complete clearance of Babesia microtti infection after 44-days of treatment with a combination of half dose of CFZ and atovaquone in immunocompromised mice. Furthermore, Ammerman et al (2018) used a half dose of CFZ to add potent bactericidal and treatment-shortening activity to the first-line regimen in M. tuberculosis -infected BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a combination of half the dose of CFZ with half the dose of NTZ. This was based on observations from previous studies of Tuvshintulga et al (2021) who reported excellent efficacy and complete clearance of Babesia microtti infection after 44-days of treatment with a combination of half dose of CFZ and atovaquone in immunocompromised mice. Furthermore, Ammerman et al (2018) used a half dose of CFZ to add potent bactericidal and treatment-shortening activity to the first-line regimen in M. tuberculosis -infected BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the radical cure of babesiosis remains challenging in severely immunocompromised patients. In the recent past, a few compounds have been reported as promising drugs against human babesiosis, namely endochin-like quinolones (ELQs) ( Lawres et al., 2016 ; Chiu et al., 2021 ), tafenoquine ( Mordue and Wormser, 2019 ; Liu et al., 2021 ), and clofazimine ( Tuvshintulga et al., 2022 ). ELQs showed inhibitory effects against apicomplexan parasites by targeting Cytb ( Doggett et al., 2012 ; Stickles et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clofazimine combined with ATO was also evaluated as a candidate for human babesiosis. Uninterrupted treatment of clofazimine with ATO resulted in the radical cure of B. microti -infected SCID mice in 44 days ( Tuvshintulga et al., 2022 ). Phosphatidylinositol kinases (PIKs) are essential in the regulation of cell proliferation, survival, and membrane trafficking ( Hassett and Roepe, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations